PERFORMANCE ANALYSIS OF REGIONAL FINANCIAL BUDGET PLANNING IN THE REGIONAL SECRETARIAT OF NORTH MINAHASA DISTRICT - Muliawahyuni Joice Kaparang; Wilson Bogar; Meidy Kantohe (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the performance of the regional financial budget planning process and identify influencing factors within the North Minahasa Regency Regional Secretariat. Using a descriptive qualitative approach, this study involved five key informants who were structural and functional officials in the Regional Secretariat and the Regional Development Planning Agency (Bappeda). Data were collected through semi-structured interviews, field observations, and document studies. Data analysis adopted the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source and document triangulation, as well as member checking. The results showed that the preparation of the Regional Work Plan (RKPD) and Regional Budget (RAPBD) documents administratively met the Ministry of Home Affairs deadline, but the substantive quality remained weak. Planning tended to be incremental and reactive, characterized by disparities in infrastructure allocation between regions, inaccurate PAD projections, and low realization of direct spending. The main inhibiting factors included suboptimal human resource capacity in preparing evidence-based justifications, short-term political dynamics, high fiscal dependency, reactive institutional coordination, and limited utilization of the Regional Budget Information System (SIPD) for administrative purposes. It was concluded that poor budget planning performance is a manifestation of the gap between procedural compliance and institutional analytical capacity. Strategic recommendations include strengthening the spatial equity-based allocation formula, optimizing the analytical features of the SIPD, improving the accuracy of fiscal forecasting, and transforming the work culture toward public value-based planning.